f(x) = x^2 + 2x - 1

g(x) = 5x + 3

Fnd the values of x for which f(x) = g (x)

Guest Mar 21, 2017

#1**+3 **

f(x) = x^{2} + 2x - 1

g(x) = 5x + 3

Find the values of x for which

f(x) = g(x)

Just substitute in what f(x) and g(x) are and solve for x.

x^{2} + 2x - 1 = 5x + 3

x^{2} + 2x - 1 = 5x + 3

Subtract 3 from both sides.

x^{2} + 2x - 4 = 5x

Subtract 5x from both sides.

x^{2} - 3x - 4 = 0

Factor.

(x + 1)(x - 4) = 0

Set each factor equal to 0.

x + 1 = 0 or x - 4 = 0

x = -1 or x = 4

hectictar
Mar 21, 2017